A chromosome-level genome assembly of Meteorus pulchricornis Wesmael (Hymenoptera: Braconidae) - Shiji Tian; Ruizhong Yuan; Xingzhou Ma; XiaoHan Shu; Yu Fang; Zhaohe Lu; Qiuyu Qu; Yu Jin; Jiabao Gong; Yanlin Peng; Ziqi Wang; Xiqian Ye; et al. (Scientific Data)
Abstract Meteorus pulchricornis Wesmael (Hymenoptera: Braconidae) is an important parasitoid of lepidopteran insects. So far, only three scaffold-level genomes have been published for the genus Meteorus. In this study, we present a high-quality, chromosome-level genome assembly of M. pulchricornis, characterized by high accuracy and contiguity. This assembly was achieved using Oxford Nanopore Technologies long-read, MGI-SEQ short-read, and Hi-C sequencing methods. The final assembly was 158.5 Mb in genome size, with 153.8 Mb (97.03%) assigned to ten pseudochromosomes. The scaffold N50 length reached 17.51 Mb, and the complete Benchmarking Universal Single-Copy Orthologs (BUSCO) score was 99.3%. The genome contains 28.29 Mb of repetitive elements, accounting for 18.39% of the total genome size. We identified 12,342 protein-coding genes, of which 12,308 genes were annotated functionally. Our investigation into gene family evolution in M. pulchricornis showed that 563 gene families expanded, 1,739 contracted, and 58 underwent rapid evolution. The high-quality genome assembly we report here is advantageous for further research on parasitoid wasps and provides a foundational data resource for natural enemy studies.